Territorial development at local scale – chosen aspects - Rogowska, Małgorzata (Rozwój terytorialny w skali lokalnej – wybrane aspekty, 2019)
Territorial development is one of the key issues promoted in the European Union’s regional policy. In a modern economy it is necessary to include the territorial approach in policy-making process at all levels, and the scale that gains importance is the local level where all processes occur. The paper presents the theoretical aspects of territorial development on a local scale, with an emphasis on the European Union’s approach to this issue
Biblioteka Regionalisty, 2019, Nr 19, s. 191-197
Keywords: Dolny Śląsk